Long-term follow-up of patients with chronic total coronary artery occlusion previously randomized to treatment with optimal drug therapy or percutaneous revascularization of chronic total occlusion (COMET-CTO) - Juricic, Stefan A.; Stojkovic, Sinisa M.; Galassi, Alfredo R.; Stankovic, Goran R.; Orlic, Dejan N.; Vukcevic, Vladan D.; Milasinovic, Dejan G.; Aleksandric, Srdjan B.; Tomasevic, Miloje V.; Dobric, Milan R.; Nedeljkovic, Milan A.; Beleslin, Branko D.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background The COMET-CTO trial was a randomized prospective study that assessed long-term follow-up in patients with chronic total occlusion (CTO) in coronary arteries treated with percutaneous coronary intervention (PCI) or with optimal medical therapy (OMT). During the 9-month follow-up, the incidence of major adverse cardiac events (MACE) did not differ between the two groups; no death or myocardial infarction (MI) was observed. There was a significant difference in quality of life (QoL), assessed by the Seattle Angina Questionnaire (SAQ), in favor of the PCI group. Here we report long-term follow-up results (56 ± 12 months). Methods Between October 2015 and May 2017, a total of 100 patients with CTO were randomized into two groups of 50 patients: PCI CTO or OMT group. The primary endpoint of the current study was the incidence of MACE defined as cardiac death, MI, and revascularization [PCI or coronary artery bypass graft (CABG)]. As the secondary exploratory outcome, we analyzed all the cause-mortality rate. Results Out of 100 randomized patients, 92 were available for long-term follow-up (44 in the PCI group and 48 in the OMT group). The incidence of MACE did not differ significantly between the two groups (p = 0.363). Individual components of MACE were distributed, respectively: cardiac death (OMT vs. PCI group, 6 vs. 3, p = 0.489), MI (OMT vs. PCI group, 1 vs. 0, p = 1), and revascularization (PCI: OMT vs. PCI group, 2 vs. 2, p = 1; CABG: OMT vs. PCI group, 1 vs. 1, p = 1). There was no significant difference between the two groups regarding the individual component of MACE. Six patients died from non-cardiac causes [five deaths were reported in the OMT group and one death in the PCI group (p = 0.206)]. Kaplan-Meier survival curves for MACE did not differ significantly between the study groups (log-rank 0.804, p = 0.370). Regarding the secondary exploratory outcome, a total of 15 patients died at 56 ± 12 months (11 in the OMT and 4 in the PCI group) (p = 0.093). The Kaplan-Meier survival curves for all-cause mortality rates did not differ significantly between the two groups (log rank 3.404, p = 0.065). There were no statistically significant differences between OMT and PCI groups in all five SAQ domains. There was a significant improvement in three SAQ domains in the PCI group: PL (p < 0.001), AF (p = 0.007), and QoL (p = 0.001). Conclusion After 56 ± 12 months of follow-up, the incidence of MACE, as well as QoL measured by SAQ, did not differ significantly between the PCI and OMT groups.